ENVIRONMENTAL ECONOMICS AND ECOSYSTEM SERVICES - Bluffstone, Randall, 1960- (Textbooks in environmental agriculture and economics., 2025)
"Environmental Economics and Ecosystem Services provides a rigorous yet accessible introduction to environmental economics, using ecosystem services as the underlying framework. Assuming no prior knowledge of economics, and using a conversational writing style, the focus is on exploring society's linkages with the environment and how economics can help solve key environmental problems. Structured in three parts, the book first introduces readers to the key theories in environmental economics and ecosystem services, and then explores the challenges of conservation. The final section examines environmental policy options, such as cap-and-trade, behavioral nudges, community-based natural resource management and carbon taxes. There is a strong international focus throughout the book, with real-life examples taken from North America, Europe, Asia, Africa and other regions. Students are supported by a range of pedagogical features, including chapter objectives, chapter summaries, discussion questions and further reading suggestions. In addition, the book offers worked examples, analytical problems and "Challenge Yourself" boxes to develop critical thinking skills. Lecture slides and answers to questions for discussion and practice problems are available for instructors. This is the ideal text for introductory courses in environmental economics, ecological economics, economics of sustainability, environmental management, environmental policy and ecosystem services"--